2021
DOI: 10.1080/15563650.2020.1842882
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness concerns of lopinavir/ritonavir in COVID-19 affected patients: a retrospective series

Abstract: Context Originally developed for treatment of human immunodeficiency virus (HIV), the antiviral combination lopinavir/ritonavir (LPV/r) is being repurposed for treating the novel coronavirus disease (COVID-19) despite minimal experience in this markedly different population and an in-vitro derived EC50 against SARS-CoV-2 several hundred-fold greater than for HIV. We present a case series including a case of severe hyponatremia and a 32-fold overdose raising safety and effectiveness concerns in COV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Additionally, lopinavir/ritonavir inhibits CYP enzyme binding, which in turn causes adverse drug reactions and increases the frequency and severity of other potential complications. 42 Lopinavir/ritonavir also affects the body’s immunoregulation which causes the initial growth of the virus to increase due to decreased immune function. 43…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, lopinavir/ritonavir inhibits CYP enzyme binding, which in turn causes adverse drug reactions and increases the frequency and severity of other potential complications. 42 Lopinavir/ritonavir also affects the body’s immunoregulation which causes the initial growth of the virus to increase due to decreased immune function. 43…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lopinavir/ritonavir inhibits CYP enzyme binding, which in turn causes adverse drug reactions and increases the frequency and severity of other potential complications. 42 Lopinavir/ritonavir also affects the body's immunoregulation which causes the initial growth of the virus to increase due to decreased immune function. 43 In a study conducted by Grimaldi et al, there was a higher incidence of acute kidney injury and the need for renal replacement therapy in patients receiving lopinavir/ritonavir, which raised doubts about its safety profile.…”
Section: Dovepressmentioning
confidence: 99%
“…In this study, LPV/RTV did not improve clinical outcomes by minimizing hospital stay, mechanical ventilation, or mortality rate. A retrospective study was conducted to observe whether the conventional dose of LPV/RTV used for HIV can be used in COVID-19 patients; it turns out dose tampering is a mandatory act to use the drug for the latter purpose [89]. Cao et al [74] conducted a randomized, controlled, open-label clinical trial (ChiCTR2000029308) on 199 patients (LPV/RTV = 99 and SOC = 100).…”
Section: Lopinavir-ritonavir (Lpv/rtv)mentioning
confidence: 99%
“…A comparative randomized clinical trial between sofosbuvir/daclatasvir (SFV/DCV) and LPV/RTV was carried out where only the discharge rate was better in the LPV/RTV group; better survival rate and fewer complications were shown in the SFV/DCV group [125]. Similarly, Lepage et al [89] and Schneider et al [90] conducted retrospective studies and found several preliminary results that warrant well-designed and more extensive randomized controlled clinical trials.…”
Section: Lopinavir-ritonavir (Lpv/rtv)mentioning
confidence: 99%
“…However, a retrospective case-series study raised concerns about the safety of lopinavir-ritonavir use in COVID-19 patients based on the possibility of causing serious adverse events even before reaching the presumed therapeutic concentration for COVID-19 treatment. Moreover, WHO reported the recommendation of Solidarity trial regarding immediate discontinuation of this combination in COVID-19 patients due to ineffectiveness and safety concerns on July 4, 2020 ( Lepage et al, 2021 ). Again, a large retrospective, multicenter study involving 8,553 COVID-19 patients found no overall advantage of lopinavir-ritonavir administration in early COVID-19 patients ( Lora-Tamayo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%